Nest sharing by captive Cape Teal Anas capensis - Bannor, Brett K (Wildfowl, 1997)
Two captive female Cape Teal deposited their eggs into a single nest and appeared to share brooding duties. Approximately 11 days elapsed between the conclusion of the first hen’s clutch and the commencement of the second hen’s clutch. When the eggs from the first hen hatched, both females left the nest to attend the ducklings. The second hen’s eggs were removed and incubation completed artificially. Although the occurrence may have been an aberration of captivity, the possibility should not be discounted that large clutches of Cape Teal eggs encountered in the wild may represent contributions form more than one hen.